A capacitação profissional dos reabilitados do INSS e a reinserção ao trabalho: uma análise a partir dos cursos ofertados pelo SENAC e SENAI de Pato Branco - PR - Palavezzini, Elisangela Isaias (2020)
Professional rehabilitation is a service offered by the Brazilian Social Securityto insured people who are incapacitated, totally or partially for work, and aims to provide the means for professional and social re-education and re-adaptation. In order to achieve this goal, the Professional Rehabilitation Service send insured people to take a professional training course, especially with the contracted institutions of Sistema S (SENAC and SENAI). In this regard, the study seeks to answer the following guiding question: What are the characteristics and dynamics of the professional training courses offered by SENAC and SENAI to the rehabilitated INSS in Pato Branco-PR, as a mean for reintegrating to work? The research is characterized as exploratory qualitative, through field research. The research participants were composed by two distinct groups: insured people rehabilitated by the INSS of Pato Branco-PR from January of 2015 to December of 2017, and who took a professional training course at SENAC or SENAI institutions, as well as the employeesat SENAC and SENAI, teachers and pedagogical coordinators linked to the investigated courses. The data were collected in order to meet the qualitative approach provided for orientation of the study, from two specific moments, the first with insured persons rehabilitated by the INSS and the second with SENAC and SENAI workers. For data collection with rehabilitated policyholders and teachers linked to System S, the focus group technique was used and individual semi-structured interviews were conducted with policyholders and teachers who were unable to participate in the focus group. Semi-structured interviews were conducted with the pedagogical coordinators of SENAC and SENAI.In total, 16 individuals participated in the research, being 08 rehabilitated, 06 teachers and 02 pedagogical coordinators. Qualitative data were analyzed and interpreted by the Content Analysis method from analytical categories defined a priori,namely: Rehabilitation and Work; Professional Training in the Sistema S; Professional Rehabilitation and Reintegration to work. With the research, it was possible to conclude that professional training courses have contributed in several aspects in the life of the insured, such as knowledge, encouragement and motivation, confidence and elevation of self-esteem. However, the reinsertion of the insured person to work has presented limits and, in most cases, it is not effectively contributing to training the insured person to a new function/activity that allows reinsertion to work.